Refugee Return, Reintegration, and Sustainable Futurity: Politics, Pitfalls and Possibilities of Repatriation in Post/Conflict Situations. Issue 3 (27th May 2023) - Um, Khatharya
ABSTRACT: With conflict and displacement among the most pressing issues of our time, refugee repatriation and reintegration are integral to post-conflict development and enduring peace. Regarded by the UN as a durable solution, repatriation has come to be viewed as the most viable option given the prevailing global landscape of increased displacement and stringency of national policies towards asylum seekers. These realities have also engendered a pragmatic turn from the principle of voluntariness to an emphasis on safety and the politicisation of the humanitarian agenda that destabilise the foundational principles of the refugee protection regime. Drawing upon the experiences of the Cambodian refugee repatriation in 1992–93, the more recent repatriation of Burmese refugees 1 from Thailand and insights from other instances of return, this paper examines the politics, pitfalls, and possibilities of Southeast Asian refugee repatriation following political settlements, prompted as they were by political and other exigencies rather than the restoration of peace and stability. With attention to the relationships between refugees, refugee originating and receiving countries, and the UNHCR, it underscores the predicament, ambivalence, and dismissal that undergird refugee return. It interrogates notions of voluntariness in the context of constrained choice, and of safe and dignified return, citizenship, and belonging in the context of fragile peace. It also reflects on the delimitation of accountability by the changing status of refugees when they re-crossed the border and argues for looking at repatriation and re-integration as a continuum, and for centering sustainability and the restoration of refugee futurity in the discourse of return.